# Equations » Trigonometric equations

The equations `sin`(A) = C and `cos`(A) = C with C = –1,0,1 you solve using the unit circle.

`sin`(A) = 0 gives A = k · π
`sin`(A) = 1 gives A = 12π + k · 2π
`sin`(A) = –1 gives A = – 12π + k · 2π

`cos`(A) = 0 gives A = 12π + k · π
`cos`(A) = 1 gives A = k · 2π
`cos`(A) = –1 gives A = π + k · 2π

The equations `sin`(A) = C and `cos`(A) = C with C = –12 , – 12 , – 12, 12, 12 , 12 you solve by reading of one solution B from the 'exact-values-circle'.

Then you use:
`sin`(A) = C gives A = B + k · 2π  or  A = π – B + k · 2π
`cos`(A) = C gives A = B + k · 2π  or  A = –B + k · 2π

Example 1
`sin`(2x – 13π) = 1
2x – 13π = 12π + k · 2π
2x = 56π + k · 2π
x = 512π + kπ

Example 2
`cos`2(x) – `cos`(x) = 0
`cos`(x) · (`cos`(x) – 1) = 0
`cos`(x) = 0  or  `cos`(x) = 1
x = 12π + kπ  or  x = k · 2π

Example 3
2`sin`(3x) = `sin`(3x) = 12 `sin`(3x) = `sin`(13π)
3x = 13π + k · 2π  or  3x = π – 13π + k · 2π
x = 19π + k · 23π  or  x = 29π + k · 23π

Example 4

2`cos`(2x – 13π) = – `cos`(2x13π) = –12 `cos`(2x13π) = `cos`(34π)
2x – 13π = 34π + k · 2π  or  2x – 13π = –34π + k · 2π
2x = 1312π + k · 2π  or  2x = –512π + k · 2π
x = 1324π + kx  or  x = –524π + kπ